2013
DOI: 10.1037/a0033248
|View full text |Cite
|
Sign up to set email alerts
|

Emotional congruence with children and sexual offending against children: A meta-analytic review.

Abstract: Emotional congruence with children is a characteristic of extrafamilial SOC, is moderately predictive of sexual recidivism, and is potentially amenable through treatment efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 64 publications
4
49
1
Order By: Relevance
“…The meta-analysis by McPhail et al (2013) found that incest offenders evidenced, on average, lower levels of emotional congruence with children than did individuals who have never committed a sexual offence against a child. This pattern might not be expected if emotional congruence with children and pedophilia were parts of the same construct.…”
Section: Discussionmentioning
confidence: 97%
“…The meta-analysis by McPhail et al (2013) found that incest offenders evidenced, on average, lower levels of emotional congruence with children than did individuals who have never committed a sexual offence against a child. This pattern might not be expected if emotional congruence with children and pedophilia were parts of the same construct.…”
Section: Discussionmentioning
confidence: 97%
“…Loneliness and social rejection are key risk factors in etiological theories of child sexual abuse [42], as well as being linked to suicidality [43], reduced intelligent thought, and decreased self-regulation [44]. As well, interacting with children to meet social, emotional, and intimacy needs, while being a strong predictor of sexual offending against a child [45], has also been linked to loneliness and social rejection in sexual offenders and may be a means that a pedophilic individual uses to reduce the experience of loneliness [46,47]. Working through the experience of loneliness and finding ways to satisfy social and intimacy needs may be key aspects of preventative treatment with non-offending pedophiles.…”
Section: Treatment With Non-offending Pedophilesmentioning
confidence: 99%
“…For example, some professionals may assess low-victim empathy and lack of motivation at treatment intake because of their relevance to the process of treatment, but neither factor predicts sexual recidivism (Hanson & Morton-Bourgon, 2005; Mann, Hanson, & Thornton, 2010). In contrast, reliable predictors of sexual recidivism include atypical sexual interests (Hanson & Morton-Bourgon, 2005), antisocial tendencies (Hawes, Boccaccini, & Murrie, 2013), emotional congruence with children (McPhail, Hermann, & Nunes, 2013), and attitudes tolerant of sexual offending (Helmus, Hanson, Babchishin, & Mann, 2013). No single risk factor provides the sufficient or necessary conditions for the persistence of sexual offending, and consequently, evaluators typically consider a range of risk factors organized into structured risk assessment tools (Archer, Buffington-Vollum, Stredny, & Handel, 2006; Kelley, Ambroziak, Thornton, & Barahal, 2018).…”
mentioning
confidence: 99%